EARLY DIAGNOSIS AND EFFECTIVENESS OF SCREENING METHODS FOR PROSTATE CANCER (Scientific Conference on Multidisciplinary Studies, 2025)
This thesis reviews prostate cancer screening methods, highlighting that systematic screening can reduce mortality by about 20%. Advanced tools like MRI-guided biopsy improve diagnosis and reduce unnecessary procedures. Combining personalized risk assessment with shared decision-making optimizes screening benefits while maintaining patient quality of life.